Detection and quantitation of synthetic cannabinoid receptor agonists in infused papers from prisons in a constantly evolving illicit market. Issue 4 (4th February 2020) - Norman, Caitlyn; Walker, Gillian; McKirdy, Brian; McDonald, Ciara; Fletcher, Daniel; Antonides, Lysbeth H.; Sutcliffe, Oliver B.; Nic Daéid, Niamh; McKenzie, Craig
Abstract: Drug misuse in prisons contributes to increased disruption and violence and negatively impacts prisoner safety, rehabilitation, and recovery. Synthetic cannabinoid receptor agonists (SCRAs), colloquially known as "spice", are infused into papers and are of particular concern in a prison setting where they are commonly vaped. Methods for the qualitative and quantitative analysis of SCRA infused papers, including impurity profiling, were developed using gas chromatography–mass spectrometry (GC–MS) with qualitative confirmation by ultra high pressure liquid chromatography with photodiode array and quadrupole time of flight mass spectrometry detection (UPLC‐PDA‐QToF‐MS) and applied to 354 individual seized paper samples originating from 168 seizures from three Scottish prisons. Of these samples, 41% (146 samples from 101 seizures) contained at least one SCRA and multiple SCRAs were detected on 23% of these papers. Concentrations ranged from < 0.05–1.17 mg/cm 2 paper, representing the first reported quantitative data for SCRA infused papers. An evolution in the SCRAs detected was demonstrated; 5F‐MDMB‐PINACA (5F‐ADB) predominated until late 2018, after which time 5F‐MDMB‐PICA and 4F‐MDMB‐BINACA became increasingly more prevalent, followed by the arrival of MDMB‐4en‐PINACA in June 2019. Concentration mapping data from two seized paper samples demonstrated that SCRA concentrations across larger papers were highly variable (0.47–2.38 mg/cm 2 paper) making consistent dosing by users, and representative sampling by laboratory analysts, difficult. Near real‐time qualitative and quantitative information on SCRAs circulating in prisons acts as an early warning system for SCRAs emerging on the wider illicit market, inform the methods used to detect them and limit supply, and provide information to support harm reduction measures. Abstract : Synthetic cannabinoid infused paper samples seized in Scottish prisons were qualitatively and quantitatively analysed and the market evolution described from June 2018 to September 2019.